Neurological Death is Common in Patients With EGFR Mutant Non-Small Cell Lung Cancer Diagnosed With Brain Metastases - Matthew Ramotar, HBSc; Sierra Barnes, BSc; Fabio Moraes, MD; Archya Dasgupta, MD; Normand Laperriere, MD; Barbara-Ann Millar, MBChB; Alejandro Berlin, MD, MSc; Tatiana Conrad, MD; Monique van Prooijen, PhD; Andrei Damyanovich, PhD; Robert Heaton, PhD; Young-Bin Cho, PhD; et al. (Advances in Radiation Oncology, 2020)
Purpose: Brain metastases (BrM) are common in patients with epidermal growth factor receptor (EGFRm) mutant non-small cell lung cancer (NSCLC). We sought to determine the rate of neurologic death (ND) in this population. Methods and Materials: We analyzed data from 198 patients who received a diagnosis of BrM from EGFRm NSCLC between 2004 and 2016, comparing patients whose initial treatment for BrM was stereotactic radiosurgery with or without tyrosine kinase inhibitors (TKI), whole brain radiation therapy (WBRT) with or without TKI, or TKI alone. The incidence of ND was determined using a competing risks analysis. Univariate and multivariate analyses were used to identify clinical variables associated with this outcome. Results: The percentage of patients who initially received stereotactic radiosurgery, whole brain radiation therapy, or TKI alone was 22%, 61%, and 17%, respectively. Median overall survival in these subgroups was 31.1, 14.6, and 24.6 months, respectively (P = .0016). The 5-year incidence of ND among all patients was 40% and did not significantly vary according to treatment group. In a multivariable model, only leptomeningeal disease at any point in a patient’s disease course significantly correlated with ND (hazard ratio 4.75, P <.001). Conclusions: Among our cohort of patients with BrM from EGFRm NSCLC, the incidence of ND was significantly higher than suggested by previous reports. BrM should be considered a driver of mortality in many patients with EGFRm NSCLC, and treatments providing better control of BrM, lower neurocognitive side effects, and maintenance of quality of life are needed.